Wasted Space: Using Parking Lots & Vacant Land to Improve Neighborhood Completeness - Ryan Martyn (Hatfield Graduate Journal of Public Affairs)
This study conducts a spatial analysis of Portland, Oregon, focusing on leveraging underutilized areas like parking lots and vacant land—termed "wasted space"—to improve the city's completeness. Central to this investigation is the concept of a "complete neighborhood," characterized by access to daily necessities within convenient active transportation trip. This comprehensive idea encompasses walkability, equitable access to services, and sustainability. This paper aims to redefine the concept of a complete neighborhood with precision and delve into its implications. The research looks at five regional, town, and neighborhood centers as defined by the city of Portland. These centers act as pivotal hubs for complete neighborhoods, housing diverse amenities like retail outlets, civic facilities, residences, healthcare centers, workplaces, and public spaces. Through these case studies, the paper explores how repurposing wasted space can contribute to the development of complete, pedestrian-friendly neighborhoods. To aid in visualizing the potential transformations proposed, architectural imagery is employed, providing insights into the potential impact on Portland neighborhoods and urban areas across the United States.